Reconstruction of the Ethics of Artificial Intelligence Development in Islamic Philosophy and Muhammadiyah Thought - Ismiyanto, Mazwar; Anif, Sofyan; Prayitno, Harun Joko; Muhibbin, Ahmad; Kusumaningtyas, Dian Artha; Handayani, Trisakti (Universitas Muhammadiyah Surakarta, 2026)
This study aims to analyze the perspectives of al-Islam and Muhammadiyah on the development of Artificial Intelligence (AI) within the framework of ethics, epistemology, and the concept of blessing (barakah). The research employs a qualitative approach using a library research method, through the analysis of literature on Islamic philosophy, Muhammadiyah thought, and studies on technology ethics and AI. The data were analyzed using content analysis and hermeneutic techniques to identify normative principles relevant to responding to AI development. The findings indicate that Islam views technology as an instrument of the human mandate of khalifah (vicegerency), which must be directed toward public welfare (maslahah), justice, and balance between worldly life and the hereafter. The concept of Islamic ethics including tawhid, adl, moral character (akhlaq), and social responsibility serves as the normative foundation for evaluating and utilizing AI. Knowledge (ilm) is understood as a religious obligation that is not morally neutral; therefore, AI development must be oriented toward truth and benefit. Meanwhile, the concept of blessing (barakah) emphasizes sustainability and the spiritual dimension in the use of technology. From the Muhammadiyah perspective, the integration of religion and science, the strengthening of education, and community empowerment constitute the primary principles in AI development. AI is positioned as a means of civilizational renewal that must be guided by ethical values to prevent injustice or dehumanization. Thus, al-Islam and Muhammadiyah offer an integrative and normative philosophical framework for directing AI development in a responsible, just, and spiritually meaningful manner.